Transient Receptor Potential Channels as an Emerging Target for the Treatment of Parkinson’s Disease: An Insight Into Role of Pharmacological Interventions - Vaidya, Bhupesh; Sharma, Shyam Sunder (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is a form of neurodegeneration characterized by the symptoms of motor deficits and cognitive decline. There are a number of therapeutics available for the treatment of PD but most of them suffer serious side effects such as bradykinesia, dyskinesia and on-off effect. Therefore, despite the availability of these pharmacological agents, PD patients continue to have inferior quality of life. This has warranted a need to look for alternate strategies and molecular targets. Recent evidence suggests the Transient Receptor Potential (TRP) channels as a potential target for the management of motor and non-motor symptoms of PD. Though still in the preclinical stages, agents targeting these channels have shown immense potential in the attenuation of behavioral deficits and signaling pathways. In addition, these channels are known to be involved in the regulation of ionic homeostasis which is otherwise disrupted in PD. Moreover, activation or inhibition of many of the TRP channels by calcium and oxidative stress has also raised the possibility of their paramount involvement in affecting the other molecular mechanisms associated with PD pathology. However, due to paucity of information available and lack of specificity, none of these agents have gone into clinical trials for the PD treatment. Considering TRP channels interaction with oxidative stress, apoptosis and excitotoxicity, TRP channels and their modulators could be considered as potential future target for the treatment of PD.